Class and climate‐change adaptation in rural India: Beyond community‐based adaptation models. (4th May 2021) - Aslany, Maryam; Brincat, Shannon
Abstract: This article explores the ways in which class structure in agrarian societies shape local adaptation responses to the impact of climate change, based on an empirical study of a village society in western Maharashtra, India. It draws on two types of fieldwork data, quantitative and qualitative, including a round of household socio‐economic survey questionnaire and qualitative semi‐structured interviews. We show that climate‐change adaptation is class specific and varies considerably amongst the different classes within the relations of production even in the same village. The local class structure shape ownership and access to natural resources, with implications for both individual adaptive capacities and attempts to organize adaptation practices at the community‐level. Specifically, adaptive practice is revealed as being largely contingent on the size of land owned and livelihood options that affects, in turn, households' adaptation capacities and their experiences of climate change. We find that whilst the village inhabitants have initiated various adaptation strategies privately, no community‐based adaptation practices could be identified. As such, we call for a more comprehensive understanding of the class nature of climate change for developing effective climate adaptation strategies at the village‐community level and especially for community‐based adaptation (CBA) models.